(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
The acanthuriform family Zanclidae, whose members are commonly known as moorish idols, has until now been comprised of two species, the extant Zanclus cornutus and the Eocene Eozanclus brevirostris. Herein, a new moorish idol, Angiolinia mirabilis n. gen. et sp., is described based on three specimens from the Eocene Pesciara site of the Bolca locality, northern Italy. Morphologically, Angiolinia mirabilis n. gen. et sp. appears to be intermediate between Eozanclus brevirostris and Zanclus cornutus and differs from them by having the following features: body depth 85–87% SL; head length 38.3–39.2% SL; third dorsal-fin spine reaching about 50% SL; pectoral disc width 23.2% SL; dorsal fin containing 31 or 32 rays; anal fin containing 26 or 27 rays; pectoral fin with 11 or 12 moderately elongate rays and caudal fin truncate. A comparative osteological analysis suggests that the family Zanclidae is defined by two morphological features, namely the presence of a broadly expanded and anteroventrally convex cleithrum forming the so-called pectoral disc together with the coracoid and having a large number of dorsal- and anal-fin rays. The Eocene acanthuriform Massalongius gazolai from Bolca represents the sister group to the Zanclidae. Within the zanclids, Eozanclus brevirostris represents the sister group to the pair formed by Angiolinia mirabilis n. gen. et sp. and Zanclus cornutus. This clade is supported by the shared possession of a single supernumerary spine on the first dorsal-fin pterygiophore, a single uroneural in the caudal skeleton, and all but the first two dorsal-fin spines distally filamentous.